RESPON PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max L. Merrill) KULTIVAR ANJASMORO TERHADAP INOKULASI CENDAWAN MIKORIZA VASIKULAR ARBUSKULAR (MVA) DAN PEMBERIAN PUPUK KALIUM - Alfandi Alfandi (JURNAL AGROTROPIKA, 2011)
The study aimed to investigate response of inoculating vasicular arbuscular mycorrhizae (VAM) fungi and K fertilizing on Soybean (Glycine max L. Merrill) growth and yield. The study was conducted at Plumbon Research Station during July – September 2009 using Anjasmoro cultivar. The experiment used completely randomized block design with 2 factors and 2 replications. The first factor was dosage of VAM, i.e. 0, 5, 10, and 15 g per planting hole. The second factor was dosage of KCl fertilizer i.e. 0, 30, 60, 90 kg ha-1. The results showed an interaction between the dosage of VAM inoculation and KCl fertilizing on root length and weight of 100 seeds. Inoculating VMA 15 g per planting hole without K fertilizing, and no inoculation of VMA but with high dosage of K fertilizer both gave highest yield of soybean of 1.33 kg per harvested plot equivalent to 1.77 ton ha-1. Key words: VAM, K dosage, soybean, yield.